Simultaneous Occurrence of The White Spot Syndrome Virus (WSSV) in Penaeus vannamei, Tegillarca granosa and Scylla serrata from Traditional Shrimp Ponds - Sari, Dinda Lintang; Haryadi, Desrina; Mile, Haeruddin Daeng (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
The White Spot Syndrome Virus (WSSV) is a generalist virus and an important pathogen of white leg shrimp (Penaeus vannamei) farming in Indonesia. The shrimp farming system with inadequate biosecurity like the traditional polyculture system may facilitate the virus to infect the invertebrate live in the pond and expand its host and vector range. White leg shrimp (P. vannamei), blood cockles (Tegillarca granosa), and mud crabs (Scylla serrata) are widely used in polyculture aquaculture. Therefore, it is necessary to determine the occurrence of WSSV in these organisms. The main aim of this research was to determine whether WSSV existed in blood cockles and crabs cultivated with White leg shrimp. The survey was conducted in polyculture ponds in Morosari village and the surrounding area. The characteristic of both ponds was the sandy mud bottom and managed using traditional methods and there were no biosecurity measures implemented. A total of 33 organisms were collected, consisting of 20 blood cockles (T. granosa), 10 white leg shrimp (P. vannamei) and 3 mud crabs (S. serrata) were obtained from two traditional polyculture pond and coastal area of Morosari, Bedono, Demak. WSSV was detected using first step and nested Polymerase Chain Reaction (PCR). WSSV DNA from selected specimens were sequenced and aligned to the published WSSV sequence in the gene bank (NCBI) using BLAST application.  The result showed that WSSV existed in the three organisms tested in Morosari area, using first step and nested PCR. There is no clinical sign appearance on each sample. Alignment results showed 100 % identity with published VP28 WSSV protein.  All results concluded that WSSV was detected simultaneously in shrimp, blood cockle and crab in the study area.